Achievement Motivation in Islamic Management Practices: Developing a Scale and Validation - Sudarti, Ken; Fachrunnisa, Olivia (International Journal of Economics, Management and Accounting, 2024)
Existing research on the relationship between work ethics and various religious faiths is growing. One of these work ethics is work motivation. This article aims to discuss the concept of the need for achievement as Islamic motivation. In addition, this study intends to introduce a series of further implementations of achievement motivation theory according to the Islamic perspective. We obtained data from 324 members of several sales teams of the Indonesian Islamic organization to validate the measurement. Our research revealed 15 indicators that measure achievement motivation from an Islamic viewpoint. Researchers and experts may utilize the findings when designing, establishing, and applying relevant job motivation from a religious standpoint so that spirituality can increase constantly in the entire workforce. Furthermore, this study provides guidelines to leaders of Islamic -based institutions to motivate their sales force by considering Islamic work ethics and religiosity